Aluminum alloy busbar for bus duct with double-sided copper cladding at the end and preparation method thereof

Through the double-sided copper clad and cold rolling process at the end, the problems of copper-aluminum composite busbars being easily broken and electrochemically corroded after being used for a long time are solved, the mechanical properties and oxidation resistance of the busbars are improved, the amount of copper is used is reduced and the reliability is enhanced.

CN118942766BActive Publication Date: 2025-04-15CIXI CHIMA METAL PRODUCTS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411426210.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-04-15
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing copper-aluminum composite busbars are prone to breaking or cracking after being used for a long time, causing safety hazards and economic losses. At the same time, electromagnetic oxidation and corrosion are prone to occur at the welds, resulting in a decrease in conductivity.

Method used

The preparation method of aluminum alloy bushing with double-sided copper-clad ends is adopted to extend the width of the copper-aluminum eutectic composite plate by transverse cold rolling, and the process joints between copper and aluminum are reduced in the longitudinal cold rolling process to reduce the possibility of electrochemical corrosion.

Benefits of technology

The mechanical properties and oxidation resistance of the copper-aluminum composite busbar are improved, the amount of copper is reduced, the peel strength of the copper clad part is enhanced, the reliability of the busbar is improved, and the problems of high costs, unreliable connections and low peel strength are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118942766B_ABST
    Figure CN118942766B_ABST
Patent Text Reader

Abstract

The present invention discloses an aluminum alloy busbar for bus duct with copper clad on both sides of the ends and a preparation method thereof, and relates to the technical field of copper-aluminum composite eutectic plate production. An aluminum alloy busbar with copper clad on both sides of the ends is produced through the steps of casting, heat treatment, cutting, transverse rolling, longitudinal rolling, striping, finished product annealing, etc. Compared with the prior art, the present application designs an aluminum alloy busbar with copper clad on both sides of the ends. Through the copper cladding technology at the ends, both ends have a copper-aluminum eutectic structure, which greatly improves the mechanical properties and oxidation resistance of the copper-aluminum composite busbar, greatly reduces the amount of copper used, and at the same time, the copper clad part has high peeling strength, and the copper layer and aluminum layer are not easy to separate, so the performance is better, and the reliability of the copper-aluminum eutectic busbar is improved. Through transverse cold rolling, the width of the copper-aluminum eutectic composite plate is extended, which solves the problem that the current equipment cannot produce large-size copper-aluminum eutectic composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-aluminum composite eutectic plate production, and in particular to a production technology of an aluminum alloy busbar with double-sided copper cladding at the end. Background Art

[0002] Busbar, also known as busbar line or busbar, busbar, is a metal conductor, mainly made of copper or aluminum and other materials with high conductivity and corrosion resistance. The main function of busbar is to effectively conduct electricity from power sources (such as transformers or generators) to various types of power loads. It is not only an important connection point for electrical equipment, such as circuit breakers, fuses, switches, etc., but also can be directly installed or connected to these components by bolts, clips or other means. Since the number of busbars required for large-scale equipment is very large, if pure copper busbars are used, the cost of busbars is unbearable for most production units; while pure aluminum busbars can reduce costs, they are easy to oxidize when used, and the connection between aluminum and aluminum at the end is unreliable. After long-term use, most of the busbars have problems in the connection part. The connection between copper and copper is more reliable than the former. For this reason, copper-clad aluminum alloy busbars of various sizes have been developed on the market. The main structure is aluminum alloy covered with copper, which can ensure reliable connection while reducing costs. Copper-aluminum composite busbar is a new type of bimetallic composite conductor with the advantages of good conductivity, low density and low price. It can replace the existing pure copper conductive busbar and can be widely used in building power distribution bus ducts, high and medium frequency heating equipment, various control cabinets and large buses in the metallurgical and chemical fields.

[0003] For large and extra-large transformers, generators or starters, the internal busbars need to be longer than 3 meters, but the existing casting and rolling process is limited by the size of the casting and rolling rollers, and can only directly produce busbars with a length of less than 1.75 meters. For ultra-long copper-aluminum composite busbars, only two or more small-sized busbars can be connected by welding for composite. However, the busbar needs to pass a large current for a long time during use. Due to the material difference and welding quality at the weld, the ultra-long copper-aluminum composite busbar may break or crack after long-term use. Once this happens, it will bring serious safety hazards and immeasurable economic losses. At the same time, electromagnetic oxidation will also occur at the weld and cause powder corrosion, resulting in increased resistance, which greatly reduces the capacity of the busbar and even makes it unusable. That is, the one-time formed busbar is far superior to the welded composite busbar in terms of both conductivity and mechanical properties.

[0004] To this end, the present application designs an aluminum alloy busbar with double-sided copper cladding at the ends. Through a new process, its length can reach 3 meters, solving the problem that current equipment cannot produce large-size copper-aluminum eutectic composite materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing an aluminum alloy busbar for a bus duct with copper-clad ends on both sides. Through the copper-clad end technology, the two ends have a copper-aluminum eutectic structure at the same time, which greatly improves the mechanical properties and oxidation resistance of the copper-aluminum composite busbar, greatly reduces the amount of copper used, and at the same time, the copper-clad part has high peeling strength, and the copper layer and aluminum layer are not easy to separate, so the performance is better, and the reliability of the copper-aluminum eutectic busbar is improved, solving the problems of high cost of existing busbars, unreliable connection of pure aluminum alloy busbars, and low peeling strength of copper-aluminum composite busbars. Through transverse cold rolling, the width of the copper-aluminum eutectic composite plate is extended, solving the problem that the current equipment cannot produce large-size copper-aluminum eutectic composite materials. The longitudinal cold rolling process is used to reduce the process seam between copper and aluminum, reducing the possibility of electrochemical corrosion.

[0006] In order to solve the above technical problems, the present invention is solved by the following technical solutions: A method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends, comprising the following steps: Step A: Adding a raw aluminum ingot into a smelting furnace for smelting treatment, heating it to 720°C~750°C to obtain molten aluminum liquid, pouring the molten aluminum liquid into a holding furnace, controlling the temperature at 720~740°C, and keeping it warm for 20~60 minutes; Step B: The copper strip is unwound on a uncoiler, and there are two copper strips on the uncoiler and they are respectively on both sides of the uncoiler. A sleeve is arranged in the center of the uncoiler to limit and separate the copper strips on both sides; Step C: The aluminum liquid after being kept warm is degassed and filtered through online processing equipment such as a degassing box and a filter box. Step D: four copper strips are respectively wound on both sides of the upper and lower rollers, and the interval between the copper strips on the same roller is the sleeve width. The copper strips are heated before entering the gap between the upper and lower rollers, and the heating temperature is not less than 50°C; Step E: aluminum liquid in the temperature range of 705°C to 715°C is injected into the gap between the upper and lower rollers under static pressure through a casting nozzle, and the injection width is the sum of the width of the copper strips on both sides of the rollers and the spacing between them; Step F: The upper and lower rollers cool the molten aluminum liquid and the copper strip and solid-liquid cast and roll to form a copper-aluminum composite slab coil with copper on both sides of the end; Step G: The copper-aluminum composite slab coil is placed in an annealing furnace for homogenization annealing, the heating temperature is 350°C to 450°C, and the annealing time is 15 to 30 hours; Step H: The length of the copper-aluminum composite slab is the rolling length of the roller. After annealing, the copper-aluminum composite slab coil is cut in the width direction according to the final product specifications and the requirements of subsequent steps; Step I: Make the movement direction of the copper-aluminum composite slab in the length direction consistent with the cold rolling mill roller The tangential rolling direction is consistent, and then the copper-aluminum composite slab is continuously cold rolled to extend the length of the slab to the required specifications, the total cold rolling reduction rate is 15% to 20%, and the rolling force is not less than 600 to 800 t; step J: the movement direction of the copper-aluminum composite slab in the width direction is consistent with the tangential rolling direction of the cold rolling mill roller, and then the copper-aluminum composite slab is cold rolled at least once until the process gap between the copper clad and the base aluminum after rolling is no more than 1 mm, and the copper-aluminum composite plate is obtained after rolling; step K: then the copper-aluminum composite plate is introduced into the slitting equipment, and slitting is performed according to the product size to obtain an aluminum alloy busbar with double-sided copper cladding at the end of the required size; step M: straightening and leveling the aluminum alloy busbar with double-sided copper cladding at the end, and then chamfering is performed by the chamfering equipment, and straightening and leveling are performed again after the chamfering is completed; step N: the aluminum alloy busbar with double-sided copper cladding at the end is placed in the annealing furnace again for annealing, the heating temperature is 300°C to 400°C, and the annealing time is 6 to 8 hours.

[0007] In the above technical scheme, preferably, in step D, the copper strip is wound around the rolling roller in the opposite direction of the casting direction, and each copper strip is equipped with a tensioning roller and a pressure roller to ensure that the four copper strips move at the same speed and that the copper strips fit tightly with the rolling roller after entering the hot rolling area.

[0008] In the above technical solution, preferably, in step D, a heating roller cooperating with the copper strip is provided on one side of the casting nozzle, and the heating roller heats the copper strip to between 100°C and 150°C.

[0009] In the above technical scheme, preferably, in step D, the copper strip is wound around the rolling roller in the same direction as the casting direction, and each copper strip is equipped with a clamping heating roller, which heats the copper strip to between 100°C and 150°C and allows the copper strip to fit tightly with the rolling roller after entering the casting area.

[0010] In the above technical solution, preferably, in step F, the cooling rate is 300°C / s to 1000°C / s.

[0011] In the above technical solution, preferably, rolling and cooling are performed only in the solid-liquid casting and rolling area.

[0012] An aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends is manufactured by a method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends. The total thickness does not exceed 7 mm, the single-sided copper cladding thickness is 5% to 35% of the total thickness, the length of a single busbar is less than 3.25 m, and the copper cladding length at both ends accounts for 5% to 15% of the total length.

[0013] In the above technical solution, preferably, the peel strength of the copper-aluminum eutectic composite part is between 30 MPa and 85 MPa, the shear strength is greater than 50 MPa, and the composite rate is 100%.

[0014] In the above technical solution, preferably, the overall conductivity of the aluminum alloy busbar is greater than 60%, and the tensile strength is greater than 150 MPa.

[0015] This application mainly produces copper-clad aluminum alloy busbars with a length of 3m or more. Compared with the existing technology, this application has two substantial characteristics. The first is the end copper-clad technology. Compared with the existing two-sided copper-clad busbars, this application greatly reduces the amount of copper used without reducing the conductivity of the same size. The second is the large-size production technology. Compared with the existing welded composite busbars, the hot-rolled busbars in this application are far superior to welded composite busbars in terms of conductivity and mechanical properties.

[0016] To this end, the technical solution of this application overcomes many technical difficulties.

[0017] When copper is coated on both sides or one side, the casting nozzle only needs to statically inject the aluminum liquid onto the copper plate or between two copper plates. The entire injection width is uniform. As long as the copper plate conveying speed, hot rolling speed and injection speed are constant, continuous hot rolling production can be achieved. However, the present application is completely different. The present application is copper coated on both sides of the end, that is, there is no copper plate in the middle position, that is, aluminum liquid actually overflows from the two ends during the aluminum liquid injection process. If the copper strip does not fit the roller tightly, especially the copper strip on the upper roller, the aluminum liquid will overflow onto the copper strip that has not entered the roller. At the same time, a total of four copper strips are required for the two end faces, and the speeds of these four copper strips must be consistent, otherwise as long as the speed of one copper strip is different, serious quality problems will occur. For this reason, the copper strip must be tightly fitted on the roller, leaving space for aluminum liquid and synchronizing the winding speeds of the four copper strips. For this reason, the present application requires an additional clamping roller to press the copper strip tightly against the roller.

[0018] The copper strip of the present application is a copper-aluminum eutectic busbar. When the rollers are hot-rolling the copper and aluminum, there is a cooling device inside the rollers, which can cool the copper-aluminum alloy. The benefit of cooling is that smaller grains can be formed and the material strength can be improved. If the temperature of copper is between 150°C and 220°C during the hot rolling of copper and aluminum, the copper atoms can obtain enough energy to migrate in a short time under high temperature to form a thicker copper-aluminum eutectic layer, thereby effectively improving the bonding strength of the copper-aluminum composite interface. However, it has been explained above that the copper strip needs to be tightly fitted on the rollers, and there is a cooling device inside the rollers. If the copper strip is preheated and then passes through the rollers, it will lose temperature before entering the hot rolling area. For this reason, the copper strip needs to be heated before entering the hot rolling area. The present application sets up two structures, one is how the copper strip is pressed and heated when entering the hot rolling area in the positive direction, and the other is how the copper strip is pressed and heated when entering the hot rolling area in the negative direction. Since the copper plate of the prior art is changed to a copper strip, that is, there is a gap between the two copper strips, the entry and exit of the copper strip greatly reduces the impact on the casting nozzle and the blank.

[0019] This application requires an improvement in the cooling system of the rolls. The original cooling system of the rolls was evenly distributed inside the rolls, that is, the cooling rate of the roll surface was consistent, but this application required the copper strip to be heated before hot rolling, which required an improvement in the cooling system of the rolls to maximize the cooling rate in the hot rolling area and reduce the cooling capacity in other areas, so as to keep the copper strip warm to the greatest extent.

[0020] The present application mainly extends the 1.6m to 1.75m billet to more than 2.8m by cold rolling. However, since the present application is not fully covered with copper, after cold rolling in the length direction, seams will appear at the contact between copper and aluminum on the billet surface. The appearance of the seams seriously affects the performance of the busbar and will cause electrochemical corrosion after long-term use. For this reason, the present application needs to be cold rolled in the width direction after cold rolling in the length direction to reduce the seams as much as possible.

[0021] This application requires secondary annealing after the cold rolling is completed. Since there is a certain internal stress during the rolling process, the strength of the composite material will be reduced. Therefore, the annealing process can reduce the residual stress, stabilize the size, reduce the tendency of deformation and cracking, and ensure that the product has good comprehensive mechanical properties and good metallurgical bonding.

[0022] Compared with the prior art, the present application designs an aluminum alloy busbar with copper clad on both sides of the ends. Through the copper cladding technology at the ends, it has a copper-aluminum eutectic structure at both ends, which greatly improves the mechanical properties and oxidation resistance of the copper-aluminum composite busbar, greatly reduces the amount of copper used, and at the same time, the copper-clad part has high peeling strength, and the copper layer and aluminum layer are not easy to separate, which has better performance and improves the reliability of the copper-aluminum eutectic busbar, solving the problems of high cost of existing busbars, unreliable connection of pure aluminum alloy busbars, and low peeling strength of copper-aluminum composite busbars. Through transverse cold rolling, the width of the copper-aluminum eutectic composite plate is extended, solving the problem that the current equipment cannot produce large-size copper-aluminum eutectic composite materials. The longitudinal cold rolling process is used to reduce the process seam between copper and aluminum, reducing the possibility of electrochemical corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a structural diagram of the double-sided copper-clad aluminum busbar at the end of this application. DETAILED DESCRIPTION

[0024] The following is a clear and complete description of the technical solutions of the various embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] like Figure 1 As shown, the double-sided copper-clad aluminum alloy busbar at the end of the present application includes a copper cladding 2 and a base aluminum alloy 1 at the upper and lower sides of the end.

[0026] Example 1: Production of 3m long and 6mm thick end double-sided copper-clad aluminum busbar, single copper length 20cm, thickness 1.5mm. The following steps are included: Step A: Add raw aluminum ingots into a smelting furnace for smelting treatment, heat to 720℃~750℃, and obtain molten aluminum liquid; pour the molten aluminum liquid into a holding furnace, control the temperature at 720~740℃, and keep it warm for 20~60min; the raw aluminum ingots are aluminum materials of model 1G20, 1050, 1060, 1100, with an aluminum content greater than 99.2% and a thickness of 16mm.

[0027] Step B: The copper strip is unwound on the unwinder. There are two copper strips on the unwinder and they are located on both sides of the unwinder. A sleeve is set in the center of the unwinder to limit the separation of the copper strips on both sides. The copper strip is T2 copper or brass with a thickness of 4mm. Before unwinding, the copper strip is first rinsed with high pressure to quickly remove solid impurities on the surface of the copper plate, and then rinsed with low pressure. The rinse liquid is an alkaline degreasing liquid at 50°C for degreasing treatment to remove grease on the surface of the copper plate. Finally, the oxide layer on the surface of the copper plate is polished off by a steel brush equipment. After polishing, the roughening degree of the copper strip surface can be improved, and the copper-aluminum composite area can be increased, thereby enhancing the bonding ability of the composite material.

[0028] Step C: After the aluminum liquid is kept still, it is degassed and filtered through online processing equipment such as degassing boxes and filter boxes. The rolls in the twin-roll casting equipment have a cooling function. It is best that the rolls are cooled only in the hot rolling area, and not outside the hot rolling area, which is conducive to the insulation of the copper strip.

[0029] Step D: Four copper strips are wound on rollers from the injection direction of the casting nozzle. Each copper strip is equipped with a tensioning roller and a pressing roller. The speed of the copper strips is adjusted by the tensioning roller and the pressing roller to ensure that the speed of the four copper strips winding on the rollers is consistent. At the same time, the pressing roller ensures that the copper strips are tightly attached to the rollers when entering the hot rolling area. There is also a heating roller on one side of the casting nozzle. Usually, one copper strip is equipped with a heating roller. The heating roller is close to the hot rolling area and heats the copper strip to 150°C.

[0030] Step E: Inject aluminum liquid in the temperature range of 710℃ into the gap between the upper and lower rollers through the casting nozzle, and the injection width is the sum of the width of the copper strips on both sides of the rollers and the distance between them; Step F: The upper and lower rollers cool the molten aluminum liquid and the copper strip and solid-liquid cast and roll to form a copper-aluminum composite slab coil with copper clad on both sides of the end; At the same time, the upper and lower rollers cool the copper-aluminum composite slab. The cooling rate is 300℃ / s. The coolant in the upper and lower rollers is water, and the water is kept at a temperature of 20℃ in the upper and lower rollers. When the aluminum liquid is injected through the casting nozzle, the aluminum liquid is rapidly cooled and solidified after contacting the rollers. Similarly, the aluminum liquid is also rapidly cooled after contacting the copper strip. The aluminum liquid and the upper and lower copper strips are contacted and crystallized in the casting and rolling area, and the heat is taken out by the cooling water circulating in the rollers.

[0031] Step G: placing the copper-aluminum composite slab into an annealing furnace for homogenization annealing at a heating temperature of 400° C. for 15 hours.

[0032] Step H: The length of the copper-aluminum composite slab is the rolling length of the roller. After annealing, the copper-aluminum composite slab is cut in the width direction according to the final product specifications and the requirements of the subsequent steps. Step I: Make the movement direction of the copper-aluminum composite slab in the length direction consistent with the tangential rolling direction of the cold rolling mill roller, and then continuously cold roll the copper-aluminum composite slab to extend the length of the slab to the required specifications. The total cold rolling reduction is 20%, and the rolling force is not less than 600t. Step J: Make the movement direction of the copper-aluminum composite slab in the width direction consistent with the tangential rolling direction of the cold rolling mill roller, and then cold roll the copper-aluminum composite slab at least once until the process gap between the copper clad and the base aluminum after rolling is no more than 1mm, and the copper-aluminum composite plate is obtained after rolling.

[0033] Step K: Then, the copper-aluminum composite plate is introduced into the slitting equipment, and the copper-aluminum eutectic transition busbar of the required size is obtained by slitting according to the product size. Step M: The copper-aluminum eutectic transition busbar is straightened and leveled, and then chamfered by the chamfering equipment, and straightened and leveled again after the chamfering is completed. Step N: The copper-aluminum eutectic transition busbar is placed in the annealing furnace again for annealing, the heating temperature is 350°C, and the annealing time is 6 hours.

[0034] Example 2: Production of 2.8m long and 7mm thick double-sided copper-clad aluminum busbar, single copper length 15cm, thickness 1mm. The following steps are included: Step A: Add raw aluminum ingots to a smelting furnace for smelting treatment, heat to 720℃~750℃, and obtain molten aluminum liquid; pour the molten aluminum liquid into a holding furnace, control the temperature at 720~740℃, and keep it warm for 20~60min; the raw aluminum ingots are aluminum materials of model 1G20, 1050, 1060, 1100, with an aluminum content greater than 99.2% and a thickness of 16mm.

[0035] Step B: The copper strip is unwound on the unwinder. There are two copper strips on the unwinder and they are located on both sides of the unwinder. A sleeve is set in the center of the unwinder to limit the separation of the copper strips on both sides. The copper strip is T2 copper or brass with a thickness of 3.5mm. Before unwinding, the copper strip is first rinsed with high pressure to quickly remove solid impurities on the surface of the copper plate, and then rinsed with low pressure. The rinse liquid is an alkaline degreasing liquid at 70°C for degreasing treatment to remove grease on the surface of the copper plate. Finally, the oxide layer on the surface of the copper plate is polished off by a steel brush equipment. After polishing, the roughening degree of the copper strip surface can be improved, and the copper-aluminum composite area can be increased, thereby enhancing the bonding ability of the composite material.

[0036] Step C: After the aluminum liquid is kept still, it is degassed and filtered through online processing equipment such as degassing boxes and filter boxes. The rolls in the twin-roll casting equipment have a cooling function. It is best that the rolls are cooled only in the hot rolling area, and not outside the hot rolling area, which is conducive to the insulation of the copper strip.

[0037] Step D: Four copper strips are respectively wound onto the rollers in the same direction from the injection direction of the casting nozzle. Each copper strip is equipped with a clamping heating roller. The clamping heating roller heats the copper strip to 150°C and allows the copper strip to fit tightly with the roller after entering the hot rolling area, while ensuring that the speed of the four copper strips winding the rollers is consistent.

[0038] Step E: Inject aluminum liquid in the temperature range of 710℃ into the gap between the upper and lower rollers through the casting nozzle, and the injection width is the sum of the width of the copper strips on both sides of the rollers and the distance between them; Step F: The upper and lower rollers cool the molten aluminum liquid and the copper strip and solid-liquid cast and roll to form a copper-aluminum composite slab coil with copper clad on both sides of the end; At the same time, the upper and lower rollers cool the copper-aluminum composite slab. The cooling rate is 300℃ / s. The coolant in the upper and lower rollers is water, and the water is kept at a temperature of 20℃ in the upper and lower rollers. When the aluminum liquid is injected through the casting nozzle, the aluminum liquid is rapidly cooled and solidified after contacting the rollers. Similarly, the aluminum liquid is also rapidly cooled after contacting the copper strip. The aluminum liquid and the upper and lower copper strips are contacted and crystallized in the casting and rolling area, and the heat is taken out by the cooling water circulating in the rollers.

[0039] Step G: placing the copper-aluminum composite slab into an annealing furnace for homogenization annealing at a heating temperature of 430° C. for 30 hours.

[0040] Step H: The length of the copper-aluminum composite slab is the rolling length of the roller. After annealing, the copper-aluminum composite slab is cut in the width direction according to the final product specifications and the requirements of the subsequent steps. Step I: Make the movement direction of the copper-aluminum composite slab in the length direction consistent with the tangential rolling direction of the cold rolling mill roller, and then continuously cold roll the copper-aluminum composite slab to extend the length of the slab to the required specifications. The total cold rolling reduction is 15%, and the rolling force is not less than 700t. Step J: Make the movement direction of the copper-aluminum composite slab in the width direction consistent with the tangential rolling direction of the cold rolling mill roller, and then cold roll the copper-aluminum composite slab at least once until the process gap between the copper clad and the base aluminum after rolling is no more than 1mm, and the copper-aluminum composite plate is obtained after rolling.

[0041] Step K: Then, the copper-aluminum composite plate is introduced into the slitting equipment, and the copper-aluminum eutectic transition busbar of the required size is obtained by slitting according to the product size. Step M: The copper-aluminum eutectic transition busbar is straightened and leveled, and then chamfered by the chamfering equipment, and straightened and leveled again after the chamfering is completed. Step N: The copper-aluminum eutectic transition busbar is placed in the annealing furnace again for annealing, the heating temperature is 350°C, and the annealing time is 7h.

[0042] Example 3: Production of 3.2m long and 6mm thick double-sided copper-clad aluminum busbar, single copper length 25cm, thickness 1.5mm. The following steps are included: Step A: Add raw aluminum ingots into a smelting furnace for smelting treatment, heat to 720℃~750℃, and obtain molten aluminum liquid; pour the molten aluminum liquid into a holding furnace, control the temperature at 720~740℃, and keep it warm for 20~60min; the raw aluminum ingots are aluminum materials of model 1G20, 1050, 1060, 1100, with an aluminum content greater than 99.2% and a thickness of 16mm.

[0043] Step B: The copper strip is unwound on the unwinder. There are two copper strips on the unwinder and they are located on both sides of the unwinder. A sleeve is set in the center of the unwinder to limit the separation of the copper strips on both sides. The copper strip is T2 copper or brass with a thickness of 2mm. Before unwinding, the copper strip is first rinsed with high pressure to quickly remove solid impurities on the surface of the copper plate, and then rinsed with low pressure. The rinse liquid is an alkaline degreasing liquid at 70°C for degreasing treatment to remove grease on the surface of the copper plate. Finally, the oxide layer on the surface of the copper plate is polished off by a steel brush equipment. After polishing, the roughening degree of the copper strip surface can be improved, and the copper-aluminum composite area can be increased, thereby enhancing the bonding ability of the composite material.

[0044] Step C: After the aluminum liquid is kept still, it is degassed and filtered through online processing equipment such as degassing boxes and filter boxes. The rolls in the twin-roll casting equipment have a cooling function. It is best that the rolls are cooled only in the hot rolling area, and not outside the hot rolling area, which is conducive to the insulation of the copper strip.

[0045] Step D: Two of the four copper strips covering the aluminum alloy are respectively wound on rollers in opposite directions from the injection direction of the casting nozzle. At the same time, both copper strips are equipped with tensioning rollers and pressing rollers. The speed of the copper strips is adjusted by the tensioning rollers and the pressing rollers. At the same time, the pressing rollers ensure that the copper strips are tightly fitted on the rollers when entering the hot rolling area. There is also a heating roller on one side of the casting nozzle. Usually, one copper strip is equipped with a heating roller. The heating roller is close to the hot rolling area and heats the copper strip to 150°C. The other two copper strips covering the bottom of the aluminum alloy are respectively wound on rollers in the same direction from the injection direction of the casting nozzle. Each copper strip is equipped with a pressing heating roller. The pressing heating roller heats the copper strip to 150°C and allows the copper strip to fit tightly with the roller after entering the hot rolling area. At the same time, the speed of the four copper strips winding the rollers is ensured to be consistent.

[0046] Step E: Inject aluminum liquid in the temperature range of 710℃ into the gap between the upper and lower rollers through the casting nozzle, and the injection width is the sum of the width of the copper strips on both sides of the rollers and the distance between them; Step F: The upper and lower rollers cool the molten aluminum liquid and the copper strip and solid-liquid cast and roll to form a copper-aluminum composite slab coil with copper clad on both sides of the end; At the same time, the upper and lower rollers cool the copper-aluminum composite slab. The cooling rate is 300℃ / s. The coolant in the upper and lower rollers is water, and the water is kept at a temperature of 20℃ in the upper and lower rollers. When the aluminum liquid is injected through the casting nozzle, the aluminum liquid is rapidly cooled and solidified after contacting the rollers. Similarly, the aluminum liquid is also rapidly cooled after contacting the copper strip. The aluminum liquid and the upper and lower copper strips are contacted and crystallized in the casting and rolling area, and the heat is taken out by the cooling water circulating in the rollers.

[0047] Step G: placing the copper-aluminum composite slab into an annealing furnace for homogenization annealing at a heating temperature of 450° C. for 630 h.

[0048] Step H: The length of the copper-aluminum composite slab is the rolling length of the roller. After annealing, the copper-aluminum composite slab is cut in the width direction according to the final product specifications and the requirements of the subsequent steps. Step I: Make the movement direction of the copper-aluminum composite slab in the length direction consistent with the tangential rolling direction of the cold rolling mill roller, and then continuously cold roll the copper-aluminum composite slab to extend the length of the slab to the required specifications. The total cold rolling reduction is 20% and the rolling force is 800t. Step J: Make the movement direction of the copper-aluminum composite slab in the width direction consistent with the tangential rolling direction of the cold rolling mill roller, and then cold roll the copper-aluminum composite slab at least once until the process gap between the copper clad and the base aluminum after rolling is no more than 1mm, and the copper-aluminum composite plate is obtained after rolling.

[0049] Step K: Then, the copper-aluminum composite plate is introduced into the slitting equipment, and the copper-aluminum eutectic transition busbar of the required size is obtained by slitting according to the product size. Step M: The copper-aluminum eutectic transition busbar is straightened and leveled, and then chamfered by the chamfering equipment, and straightened and leveled again after the chamfering is completed. Step N: The copper-aluminum eutectic transition busbar is placed in the annealing furnace again for annealing, the heating temperature is 350°C, and the annealing time is 6 to 8 hours.

[0050] The components of the copper-aluminum eutectic layer compound in the above-mentioned embodiments 1 to 3 include: Al2 Cu, Al4 Cu9, and the interface layer thickness of the eutectic layer is 300nm-500nm. The conventional shear strength of the eutectic composite material is greater than 50MPa, the conventional peel strength is 30MPa-85MPa, the conductivity of the aluminum alloy busbar is greater than 60%, and the tensile strength is greater than 150Mpa.

Claims

1. A method for preparing an aluminum alloy busbar for a bus duct with copper clad ends on both sides, characterized in that: The main body of the busbar is made of aluminum alloy, and the upper and lower ends of the aluminum alloy are covered with copper. There is a eutectic layer between the copper and aluminum alloy. The length of a single busbar is not more than 3.25m, and the length of the copper covering at both ends accounts for 5% to 15% of the total length. The thickness of the single-sided copper covering is 5% to 35% of the total thickness. It includes the following steps: Step A: adding the raw aluminum ingot into a smelting furnace for smelting treatment, heating to 720°C to 750°C to obtain molten aluminum liquid, pouring the molten aluminum liquid into a holding furnace, controlling the temperature at 720°C to 740°C, and keeping the temperature for 20 to 60 minutes; Step B: The copper strip is unwound on the unwinding machine. There are two copper strips on the unwinding machine and they are located on both sides of the unwinding machine. A sleeve is arranged in the center of the unwinding machine to limit and separate the copper strips on both sides. Step C: The aluminum liquid after being kept still is degassed and filtered through a degassing box and a filter box; Step D: four copper strips are respectively wound on both sides of the upper and lower rollers, and the interval between the copper strips on the rollers is the sleeve width; Step E: injecting aluminum liquid in a temperature range of 705°C to 715°C into the gap between the upper and lower rollers under static pressure through a casting nozzle, and the injection width is the sum of the width of the copper strips on both sides of the rollers and the distance between them; Step F: The upper and lower rollers cool the molten aluminum and copper strip and perform solid-liquid casting to form a copper-aluminum composite sheet coil with copper clad on both sides of the ends; Step G: placing the copper-aluminum composite sheet blank coil into an annealing furnace for homogenization annealing, the heating temperature is 350° C. to 450° C., and the annealing time is 15 h to 30 h; Step H: The length of the copper-aluminum composite slab is the length of the rolling roller. After annealing, the copper-aluminum composite slab coil is cut in the width direction according to the final product specifications and the requirements of subsequent steps; Step I: making the movement direction of the copper-aluminum composite slab in the length direction consistent with the tangential rolling direction of the cold rolling mill roll, then continuously cold rolling the copper-aluminum composite slab to extend the slab length to the required specifications, with a total cold rolling reduction of 15% to 20% and a rolling force of not less than 600 t to 800 t; Step J: making the movement direction of the copper-aluminum composite slab in the width direction consistent with the tangential rolling direction of the cold rolling mill roller, and then cold rolling the copper-aluminum composite slab at least once until the process gap between the copper cladding and the base aluminum after rolling is no more than 1 mm, and obtaining the copper-aluminum composite plate after rolling; Step K: Then, the copper-aluminum composite plate is introduced into a stripping device, and stripped according to the product size to obtain an aluminum alloy busbar with copper clad on both sides of the ends of the required size; Step M: straighten and level the aluminum alloy busbar with copper clad on both sides of the end, then chamfer it with a chamfering device, and straighten and level it again after the chamfering is completed; Step N: The aluminum alloy busbar with copper clad on both sides of the end is placed in the annealing furnace again for annealing at a heating temperature of 300° C. to 400° C. for an annealing time of 6 h to 8 h.

2. The method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the end according to claim 1, characterized in that In step D, the copper strip is wound around the rollers in the opposite direction of the casting and rolling direction. At the same time, each copper strip is equipped with a tensioning roller and a pressure roller to ensure that the four copper strips move at the same speed and that the copper strips fit tightly with the rollers after entering the hot rolling area.

3. The method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends according to claim 1, characterized in that: In step D, a heating roller cooperating with the copper strip is provided on one side of the casting nozzle, and the heating roller heats the copper strip to between 100°C and 150°C.

4. The method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the end according to claim 1, characterized in that In step D, the copper strip is wound around the roller in the same direction as the casting direction, and each copper strip is equipped with a clamping heating roller, which heats the copper strip to between 100°C and 150°C and allows the copper strip to fit tightly with the roller after entering the casting area.

5. The method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends according to claim 1, characterized in that: In step F, the cooling rate is 300° C. / s to 1000° C. / s.

6. A method for preparing an aluminum alloy busbar for a bus duct with double-sided copper cladding at the ends according to any one of claims 1 to 5, characterized in that: Rolling and cooling are only carried out in the solid-liquid casting and rolling area.

Citation Information

Patent Citations

  • High-performance copper-aluminum interface eutectic composite material and preparation method thereof

    CN117227274A

  • Copper-aluminum-copper composite board solid-liquid cast-rolling composite production line and production method

    CN118321341A

  • Prodn. process for casting and rolling medium plate

    CN1757454A

  • Cuprum-covered joint aluminum bus-bars

    CN201204069Y